2018
DOI: 10.1016/j.jhealeco.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Is it good to be too light? Birth weight thresholds in hospital reimbursement systems

Abstract: Birth weight manipulation has been documented in per-case hospital reimbursement systems, in which hospitals receive more money for otherwise equal newborns with birth weight just below compared to just above specific birth weight thresholds. As hospitals receive more money for cases with weight below the thresholds, having a (reported) weight below a threshold could benefit the newborn. Also, these reimbursement thresholds overlap with diagnostic thresholds that have been shown to affect the quantity and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 20 publications
0
26
0
1
Order By: Relevance
“…We thus are able to analyze whether subjects-in order to receive the maximum 8 We are aware that the payment assumption somewhat abstracts from the real world. 9 This assumption seems reasonable, in light of recent empirical evidence by, for example, Reif et al (2018), which indicates that financial incentives related to the birth weight thresholds do not directly impact the medical care that newborns receive. However, it seems reasonable to assume that they at least indirectly benefit from upcoding.…”
Section: Designmentioning
confidence: 99%
See 3 more Smart Citations
“…We thus are able to analyze whether subjects-in order to receive the maximum 8 We are aware that the payment assumption somewhat abstracts from the real world. 9 This assumption seems reasonable, in light of recent empirical evidence by, for example, Reif et al (2018), which indicates that financial incentives related to the birth weight thresholds do not directly impact the medical care that newborns receive. However, it seems reasonable to assume that they at least indirectly benefit from upcoding.…”
Section: Designmentioning
confidence: 99%
“…In credence goods markets, goods and services are provided by an expert who has an informational advantage about the quality a consumer needs. This assumption is motivated by recent empirical findings that indicate that upcoding in neonatal care does not affect the medical service provision (Jürges & Köberlein, 2015;Reif et al, 2018). In a health care market with regulated prices, physicians act as experts and insured patients seek medical care.…”
Section: Contribution To the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…For example, a newborn might receive more or better treatment because more financial resources become available through upcoding. Recent research by Reif et al (2018) has indicated that this is not the case, but we believe that further research in this direction is needed. Understanding both costs and benefits of upcoding is required for a holistic economic assessment.…”
Section: Resultsmentioning
confidence: 86%